T-DNAreader: fast and precise identification of T-DNA insertion sites in plant genomes using RNA sequencing data - Hongwoo Lee; Pil Joon Seo (Genome Biology)
Abstract Agrobacterium-mediated plant transformation, which enables the delivery of DNA using transfer DNA (T-DNA) binary vectors, is an essential technique in plant research. T-DNAs randomly integrate into the host genome, and multiple T-DNAs can sometimes integrate during a single transformation, necessitating the development of tools to elucidate the T-DNA insertion sites (TISs). Here, we present T-DNAreader, which identifies TISs from RNA sequencing data with high precision, sensitivity, and speed, outperforming existing tools. T-DNAreader enables the efficient and reliable identification of TISs within transcribed regions and standardizes the characterization of T-DNA-containing transgenic plants, which can be expanded to various organisms containing T-DNA.